Business models, circular and green economy towards sustainability. A systematic literature review. - Trequattrini, Raffaele; Lombardi, Rosa; Manzari, Alberto; Roberto, Fabiana (Piccola Impresa / Small Business, 2021)
The paper presents a systematic literature review (SLR) on the connection between business models and the adoption of the circular economy and the green economy towards sustainability. A classification is offered through which it is possible to understand the environmental, economic and social advantages that these components would beable to bring to the enterprise. We used the Scopus, Web of Science, PubMed and Google Scholar databases as the main source to collect papers. Initially, 387 papers were collected. Subsequently, we proceeded to review the contributions and, once the selection criteria were outlined, we analyzed and classified 84 publications as priorities. The SLR is performed through a bibliometric analysis using VOSviewer software. Finally, we elaborated the state of the art of this research topic for the future agenda.